Aplicación de estrategias para la conservación de la diversidad Avi-Faunística en dos áreas del campus Politécnico el Limón - Viteri Zambrano, Stefany Dolores (2023)
The objective of this study was to apply strategies for the conservation of avian-faunal diversity in two areas of the polytechnic campus at ESPAM MFL. This was a field and bibliographic-documentary research, for which the implementation of the prioritized strategies was carried out, these strategies were determined under a panel of seven experts. The conservation category of the species was identified, for which the selection of species in common was made through the taxonomic classification of 67 species between both areas, determining the presence of 27 families in CIIDEA and 25 in the Environmental career, in addition, it was indicated through the Red Book of birds that there are five species in a state of conservation almost threatened and two vulnerable species. Finally, the application of the strategies, through a survey, evaluated the knowledge acquired by 47.77% of students and teachers, whose results indicated a medium and high value through the information provided in the murals exhibited in the Environmental career. Finally, the conservation information identified was related to the application of the biotic integrity index, which indicated excellent integrity, with 32 points for CIIDEA 32 and 28 points for Environment, while the evaluation between environmental quality and the human disturbance index indicated values for CIIDEA of 0.728 and for Environment of 1.424.